Understanding Effect of Ayurvedic Treatment in Prameha (Diabetes Mellitus) and its Upadrava (Complications) (AYUSHDHARA, 2024)
Prameha is a syndrome described in the ancient Ayurvedic texts that includes clinical conditions involving metabolic syndrome and is said to be a Santarapanajanya Vyadhi. Prameha literary means anomalies of urinary secretions. On the basis of clinical features of Prameha, it correlates with diabetes mellitus. Diabetes mellitus is a metabolic cum vascular syndrome of multiple etiologies characterised by chronic hyperglycemia. The disease Prameha can be understood as having three stages based on the severity of Dhatudusti. With the Dushti of all Dhatus, Upadrava of Prameha are manifested. Case: Present case study deals with a female patient 49 years old suffering from increased frequency of micturition during night and Parshvashool with coughing from 3 years. On taking a detailed history it was found that, it was Upadrava of Prameha. Treatment protocol: Patient was given Pradhamana Nasyam with Pippali Churna after proper intervention of Snehana and Nadi Swedan on chest, supraclvicular region, and Kati Pradesh on empty stomach in the early morning. After that a freshly prepared Kwatha about 50ml of Kalmegh Churna, Punarnavamool, Giloy and Shunthi was given at BD dose. And the same drugs were used for Lepan on Kati Pradesh. Results: Parshvashool and coughing was completely cured, BSF and PPBS came to its normal range, creatinine level decreased and there was a significant reduction in fatty liver. Conclusion: With proper therapy, drug intervention, diet control and exercise Prameha and its Upadrava can be managed successfully.